2017
DOI: 10.1080/2162402x.2017.1295903
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical efficacy of immune-checkpoint monotherapy does not recapitulate corresponding biomarkers-based clinical predictions in glioblastoma

Abstract: Glioblastoma (GBM) is resistant to most multimodal therapies. Clinical success of immune-checkpoint inhibitors (ICIs) has spurred interest in applying ICIs targeting CTLA4, PD1 or IDO1 against GBM. This amplifies the need to ascertain GBM's intrinsic susceptibility (or resistance) toward these ICIs, through clinical biomarkers that may also "guide and prioritize" preclinical testing. Here, we interrogated the TCGA and/or REMBRANDT human patient-cohorts to predict GBM's predisposition toward ICIs. We exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 64 publications
2
64
0
Order By: Relevance
“…Further studies will be needed to determine whether therapeutic drug combinations to manipulate these factors will, in turn, directly impact intratumoral immune cytolytic activity and lead to an immune-mediated anti-tumor effect. Consistent with other studies [7,27,35], we found no association between the non-synonymous TMB and the degree of intratumoral immune cytolytic activity in GBM.…”
Section: Discussionsupporting
confidence: 92%
“…Further studies will be needed to determine whether therapeutic drug combinations to manipulate these factors will, in turn, directly impact intratumoral immune cytolytic activity and lead to an immune-mediated anti-tumor effect. Consistent with other studies [7,27,35], we found no association between the non-synonymous TMB and the degree of intratumoral immune cytolytic activity in GBM.…”
Section: Discussionsupporting
confidence: 92%
“…1 and Table 1) -a cancer type that appears to be particularly resistant to ICBs but responsive to DC-based vaccines. 184,187,241 Interestingly, recombinant TAAs, TAA-derived peptides and tumor-cell lysates remain the preferred source of antigens for loading DCs for DC-based vaccines across both published and ongoing clinical studies ( Fig. 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we analyze the broad impact of cancer immunotherapies including immune checkpoint blockers (ICBs), 179,180 and adoptive T-cell transfer (ACT) 181,182 on the field of DC-based vaccines. 183,184 Indeed, ongoing clinical trials are identifying a niche for DC-based vaccines in a cancer immunotherapy landscape dominated by ICBs and ACT.…”
Section: Introductionmentioning
confidence: 99%
“…C or CD8 C T cells, amongst others; [251][252][253] (2) the circulating levels of multiple cytokines, such as interferon, gamma (IFNG; best known as IFN-g), 254 IL6, 255 and tumor necrosis factor (TNF); 256-258 (3) the amounts of TAA-specific T cells (via tetramer assays); 259,260 (4) the tumor mutational load and/or the abundance of predicted neo-antigens (via genome or whole-exome sequencing); 115,138,[261][262][263][264][265] and (5) the levels of circulating biomarkers of ICD (via proteomic or metabolomic assays).…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…[105][106][107][108][109][110] Accordingly, RCD can no longer be perceived as immunogenic when: (1) the intracellular stress responses regulating the emission of ICD-associated DAMPs are pharmacologically or genetically ablated in cancer cells; or (2) when the molecular machinery dedicated to DAMP detection is inhibited or ablated. 13,44,84,91,93,97 Moreover, ICD-driven immunity can no longer operate in the presence of general immunological defects, 111 such as (1) an intrinsically low antigenicity of cancer cells, owing to low levels of TAAs or downregulation of MHC Class I molecules [112][113][114][115][116][117][118][119] ; (2) an increased immunological tolerance of the host, secondary to increased amounts of immunosuppressive cytokines, [120][121][122][123][124][125][126][127][128] or inhibitors of chemotaxis, [129][130][131][132][133][134] increased tumor infiltration by immunosuppressive cell populations, [135][136][137][138][139][140]…”
Section: Introductionmentioning
confidence: 99%